Clinical Impact of EUS-Guided Fine Needle Biopsy Using a Novel Franseen Needle for Histological Assessment of Pancreatic Diseases - Takuya Ishikawa; Hiroki Kawashima; Eizaburo Ohno; Hiroyuki Tanaka; Daisuke Sakai; Tadashi Iida; Ryo Nishio; Takeshi Yamamura; Kazuhiro Furukawa; Masanao Nakamura; Ryoji Miyahara; Senju Hashimoto; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Several studies have shown the benefits of endoscopic ultrasound-guided fine needle biopsy (EUS-FNB) using a Franseen needle for histological assessment. However, studies focusing on pancreatic diseases are limited and the safety of this method has not been well assessed. We aimed to assess the current status and issues of EUS-FNB in the diagnosis of pancreatic diseases. Materials and Methods. We retrospectively reviewed 87 consecutive EUS-FNB specimens using either a 22-gauge Franseen needle (Group A, N = 51) or a conventional 22-gauge fine-needle aspiration needle (Group B, N = 36) for pancreatic diseases, and the diagnostic accuracy and safety were compared. Final diagnoses were obtained based on surgical pathology or a minimum six-month clinical follow-up. Results. Although the diagnostic accuracy for malignancy was 96.1% in Group A versus 88.9% in Group B, with no statistically significant difference (P = 0.19), the median sample area was significantly larger in Group A (4.07 versus 1.31mm2, P < 0.0001). There were no differences between the two needles in the locations from which the specimens were obtained. Adverse events occurred in one case (2%) in Group A (mild pancreatitis) and none in Group B with no statistical significance (P = 0.586). Although there was no case of bleeding defined as adverse events, 2 cases in Group A showed active bleeding during the procedure with increase in the echo-free space, which required CT scanning to rule out extravasation. Eventually, the bleeding stopped spontaneously. Conclusions. Given its guaranteed ability to obtain core specimens and comparable safety, and although the risk of bleeding should be kept in mind, EUS-FNB using a Franseen needle is likely to become a standard procedure for obtaining pancreatic tissue in the near future.